Existência de oscilações forçadas em equações diferenciais do tipo neutro - Peneireiro, João Batista (1977)
In this work we prove a general theorem on existence and ultimately uniform boundedness of periodic solutions for a fairly general class of Functional Differential Equations of Neural Type with applications to mathematical models for a loseless transmission line. We also obtain some results on existence of forced oscilations for a retarded equation which is the mathematical model for an eletronic amplifier under effects of non-linearities.